2014
DOI: 10.1111/aor.12413
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Venoarterial Perfusion Using a Novel Synchronized Cardiac Assist Device Augments Coronary Artery Blood Flow During Ventricular Fibrillation

Abstract: Patients with cardiogenic shock have a very high mortality. Here we report the first use of a percutaneous pulsatile cardiac assist device, based on a diagonal pump synchronized with the heart cycle by means of an electrocardiographic signal in adult pigs. Eight domestic pigs underwent mandatory ventilation. During sinus rhythm, there were no differences between pulsatile and nonpulsatile perfusion with regard to pulmonary artery pressure, pulmonary wedge pressure, central venous pressure, mean arterial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 19 publications
4
33
1
1
Order By: Relevance
“…In a separate recent study, other investigators have shown that this particular i-cor system with the highest possible quality of pulsatility settings was able to restore and significantly increase systemic coronary circulation during ventricular fibrillation in an adult swine model (17). However, the objective of this initial study is to evaluate whether ECG signal of regular and irregular cardiac rhythm can trigger pulsatile mode.…”
Section: Limitationsmentioning
confidence: 99%
“…In a separate recent study, other investigators have shown that this particular i-cor system with the highest possible quality of pulsatility settings was able to restore and significantly increase systemic coronary circulation during ventricular fibrillation in an adult swine model (17). However, the objective of this initial study is to evaluate whether ECG signal of regular and irregular cardiac rhythm can trigger pulsatile mode.…”
Section: Limitationsmentioning
confidence: 99%
“…Yet ECLS itself also is prone to complications. Recent evidence supports that pulsatile flow in acute and chronic patients leads to increased perfusion of vital organs, better microcirculation, and overall improved patient outcomes compared with nonpulsatile flow (10)(11)(12)(13)(14)(15)(16)(17). As time goes on, new techniques in ECLS have been proven to decrease patient mortality and morbidity (4,6,7).…”
Section: Thoughts and Progress E134mentioning
confidence: 99%
“…The novel i-cor circuit incorporates a new diagonal pump that can produce excellent pulsatility (17,21,22). The novel i-cor circuit incorporates a new diagonal pump that can produce excellent pulsatility (17,21,22).…”
Section: Thoughts and Progress E134mentioning
confidence: 99%
See 2 more Smart Citations